Xyloglucan endo-Transglycosylase-Mediated Xyloglucan Rearrangements in Developing Wood of Hybrid Aspen(1)([W])([OA]) - Nishikubo, Nobuyuki (American Society of Plant Biologists, 2011)
Xyloglucan endo-transglycosylases (XETs) encoded by xyloglucan endo-transglycosylases/hydrolase (XTH) genes modify the xyloglucan-cellulose framework of plant cell walls, thereby regulating their expansion and strength. To evaluate the importance of XET in wood development, we studied xyloglucan dynamics and XTH gene expression in developing wood and modified XET activity in hybrid aspen (Populus tremula × tremuloides) by overexpressing PtxtXET16-34. We show that developmental modifications during xylem differentiation include changes from loosely to tightly bound forms of xyloglucan and increases in the abundance of fucosylated xyloglucan epitope recognized by the CCRC-M1 antibody. We found that at least 16 Populus XTH genes, all likely encoding XETs, are expressed in developing wood. Five genes were highly and ubiquitously expressed, whereas PtxtXET16-34 was expressed more weakly but specifically in developing wood. Transgenic up-regulation of XET activity induced changes in cell wall xyloglucan, but its effects were dependent on developmental stage. For instance, XET overexpression increased abundance of the CCRC-M1 epitope in cambial cells and xylem cells in early stages of differentiation but not in mature xylem. Correspondingly, an increase in tightly bound xyloglucan content was observed in primary-walled xylem but a decrease was seen in secondary-walled xylem. Thus, in young xylem cells, XET activity limits xyloglucan incorporation into the tightly bound wall network but removes it from cell walls in older cells. XET overexpression promoted vessel element growth but not fiber expansion. We suggest that the amount of nascent xyloglucan relative to XET is an important determinant of whether XET strengthens or loosens the cell wall.